Pemanfaatan Financial Technology dalam Pengelolaan Keuangan pada UMKM di Wilayah Depok - Kurniawan Raharjo; Nia Daliana Dalimunte; Nugroho Adhe Purnomo; Muhamad Zen; Tiffani Novia Rachmi; Nardi Sunardi; Zulfitra (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
The general objective in this community service activity is to assist MSME actors by providing training and practical knowledge of management science in financial management and the use of financial technology which has an impact on the development of Micro, Small and Medium Enterprises (MSMEs). The method used is the method of collecting data and delivering direct material as well as simulations and consultations on financial management and the use of financial technology in the development of Micro, Small and Medium Enterprises (MSMEs) which have an impact on the welfare of the community. The results of this community service activity in the effort to assist and develop MSMEs show that the use of Fintech by MSME actors can facilitate financial transactions such as payment methods for buying and selling products that are already digital, digitally storing funds becomes practical and fast, and also making it easier for MSME actors in seeking funding/business capital. The conclusion of this community service is that MSME actors can better understand and apply simple financial management methods and take advantage of financial technology to achieve prosperity and development of Micro, Small and Medium Enterprises (MSMEs).